Dari Khalayak pengguna ke Interaksi: Strategi Content Creator Kuliner di Yogyakarta dalam Membangun Engagement - Falha Kaysa; Puji Rianto (Jurnal Mahasiswa Komunikasi Cantrik, 2024)
The popularity of social media has led to professions in the field of communication, including content creators. A content creator is a profession within the digital media sphere that plays a crucial role in conveying messages through visual and audio-visual products. This research aims to identify strategies to increase engagement on the Instagram platform used by culinary content creators in Yogyakarta. The study uses a case study approach on the culinary accounts @kulineryogya, @javafoodie, @mahasiswakulineran, and @riderkulineran on Instagram. Data was collected using observation, interviews, and documentation methods. The results show that all four content creators meet all the dimensions of effective message packaging on social media according to Majid et al. (2019) and use almost identical strategies. The commonality among these content creators is building the dimensions of interactivity, credibility, and infotainment on their Instagram pages. The difference lies in their levels of personal branding, resulting in varying follower counts.